Cultural service delivery in forensic mental health services - McKenna, Brian (Seminars in forensic psychiatry, 2024)
As contentious as the writings of Samual Huntingdon might be, the quote that opens this chapter epitomises the challenges faced in developing twenty-first-century forensic mental health services (FMHS) to be culturally responsive. Indigenous peoples and other ethnic minorities are increasingly recognised as being disproportionately represented in criminal justice, mental health and FMHS settings. The inadequacy of Western paradigms and systems to meet their needs is evident. In Canada, for example, the Supreme Court recently ruled that the Correctional Service breached its statutory duty to an Indigenous prisoner in assessing his risk of recidivism using actuarial risk assessment tools not validated with Indigenous peoples.